2012
DOI: 10.1371/journal.pone.0038226
|View full text |Cite
|
Sign up to set email alerts
|

A LOV Protein Modulates the Physiological Attributes of Xanthomonas axonopodis pv. citri Relevant for Host Plant Colonization

Abstract: Recent studies have demonstrated that an appropriate light environment is required for the establishment of efficient vegetal resistance responses in several plant-pathogen interactions. The photoreceptors implicated in such responses are mainly those belonging to the phytochrome family. Data obtained from bacterial genome sequences revealed the presence of photosensory proteins of the BLUF (Blue Light sensing Using FAD), LOV (Light, Oxygen, Voltage) and phytochrome families with no known functions. Xanthomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 82 publications
3
107
0
Order By: Relevance
“…Bacteria have evolved a repertoire of sensory proteins that may detect environmental signals such as bacterial cell density or the presence of chemoattractants or chemorepellents, oxygen, and light (80,90). The total number of sensory and signaling proteins encoded by a bacterial genome was proposed as a measure of the adaptive potential of the bacterium, i.e., its intelligence quotient (IQ) (49).…”
Section: Sensors Of the Environment And Taxismentioning
confidence: 99%
“…Bacteria have evolved a repertoire of sensory proteins that may detect environmental signals such as bacterial cell density or the presence of chemoattractants or chemorepellents, oxygen, and light (80,90). The total number of sensory and signaling proteins encoded by a bacterial genome was proposed as a measure of the adaptive potential of the bacterium, i.e., its intelligence quotient (IQ) (49).…”
Section: Sensors Of the Environment And Taxismentioning
confidence: 99%
“…Following autophosphorylation, the P. syringae LOV-HK protein rapidly transferred the phosphate to this RR domain, at least when the domains were cloned separately (30). This domain structure is found primarily in bacterial plant pathogens (31). …”
Section: Introductionmentioning
confidence: 99%
“…On: Thu, 04 Apr 2019 13:22:49 glucan biosynthesis (Malamud et al, 2012), a twocomponent signal transduction system encoded by colS/ colR (Yan & Wang, 2011) and a LOV protein (Kraiselburd et al, 2012) are the elements found to be a requirement for Xcc biofilm.…”
Section: Introductionmentioning
confidence: 99%